Does super deduction R&D ﬁnancial policy in the pandemic Covid-19 give a super reaction? - Cahyani Tunggal Sari; Eni Puji Estuti; Ariyani Indriastuti (Journal of Business & Banking, 2021)
This research was motivated by the announcement of the super deduction R&D ﬁnan- cial policy (PMK 153/2020) issued by the Indonesian government during the Covid-19in 2020. This study tried to test and empirically prove either the presence or absence ofabnormal returns on the day around the announcement, before and after the announce-ment optimal portfolio of pharmaceutical and health sector stocks during the observationtime around the announcement of the super deduction R&D ﬁnancial policy. This isa quantitative research with event study using hypothesis testing from one samplet-test and paired sample t-test. The results showed that there was 1 day of observation,which indicated an abnormal return around the announcement day. Overall, beforeand after being announced based on the results of the paired sample t-test, it did notshow any abnormal returns. The highest optimal portfolio analysis is on stock of Darya Varia Laboratoria company which have a weighting of 40.86% and there are two stocks that are not optimal. This study shows that there is a reaction of market participants to pharmaceutical and health stocks on the announcement even though the reaction is very small. Based on the result, there is a need for information related to research and development activities of pharmaceutical and health companies for investors if they want to improve their stock performance.